Multi-gene panel testing increases germline predisposing mutations’ detection in a cohort of breast/ovarian cancer patients from Southern Italy - Nunziato, Marcella; Di Maggio, Federica; Pensabene, Matilde; Esposito, Maria Valeria; Starnone, Flavio; De Angelis, Carmine; Calabrese, Alessandra; D’Aiuto, Massimiliano; Botti, Gerardo; De Placido, Sabino; D’Argenio, Valeria; Salvatore, Francesco (Frontiers in Medicine, 2022)
Breast cancer is the most common neoplasia in females worldwide, about 10% being hereditary/familial and due to DNA variants in cancer-predisposing genes, such as the highly penetrant BRCA1/BRCA2 genes. However, their variants explain up to 25% of the suspected hereditary/familial cases. The availability of NGS methodologies has prompted research in this field. With the aim to improve the diagnostic sensitivity of molecular testing, a custom designed panel of 44 genes, including also non-coding regions and 5’ and 3’ UTR regions, was set up. Here, are reported the results obtained in a cohort of 64 patients, including also few males, from Southern Italy. All patients had a positive personal and/or familial history for breast and other cancers, but tested negative to routine BRCA analysis. After obtaining their written informed consent, a genomic DNA sample/patient was used to obtain an enriched DNA library, then analyzed by NGS. Sequencing data analysis allowed the identification of pathogenic variants in 12 of tested patients (19%). Interestingly, MUTYH was the most frequently altered gene, followed by RNASEL, ATM, MSH6, MRE11A and PALB2 genes. The reported results reinforce the need for enlarged molecular testing beyond BRCA genes, at least in patients with a personal and familial history, strongly suggestive for a hereditary/familial form. This gives also a hint to pursue more specific precision oncology therapy